Response‐adapted zanubrutinib and tislelizumab as a potential strategy to enhance CD19 CAR T‐cell therapy in relapsed/refractory large B‐cell lymphoma: A retrospective observational study - Rong Shen; Wei‐Guo Cao; Li Wang; Ling‐Shuang Sheng; Yi‐Lun Zhang; Wen Wu; Peng‐Peng Xu; Shu Cheng; Meng‐Ke Liu; Yan Dong; Yue Wang; Xiang‐Qin Weng; et al. (Clinical and Translational Medicine)
Abstract Background CD19 chimeric antigen receptor (CAR) T‐cell therapy is a potential treatment for relapsed/refractory (R/R) large B‐cell lymphoma (LBCL). The combination of targeted therapeutic strategies, particularly bruton tyrosine kinase inhibitor zanubrutinib and programmed death‐1 inhibitor tislelizumab, may improve clinical outcomes and modulate the tumour microenvironment (TME). Methods We studied patients with R/R LBCL who received response‐adapted zanubrutinib plus tislelizumab upon CD19 CAR T‐cell therapy between June 2021 and March 2023. Patients were treated with zanubrutinib daily from leukapheresis to day 28 post‐infusion; those achieving complete response continued zanubrutinib monotherapy for 3 months, while partial responders received combined zanubrutinib for 3 months and tislelizumab for up to 2 years. We evaluated the overall response rate (ORR), complete response rate (CRR), progression‐free survival (PFS), overall survival (OS), and safety. DNA sequencing and RNA sequencing were performed on available tumour samples to analyse genetic aberrations and TME characteristics. Results A total of 54 patients with LBCL were included, with a median follow‐up of 23.6 months. The ORR at day 28, month 3, and month 6 were 94% (CRR 66%), 87% (CRR 80%), and 80% (CRR 76%), respectively. The 2‐year PFS and 2‐year OS rates were 68% and 76%, respectively. Median PFS and median OS were not reached. Grade ≥ 3 cytokine release syndrome occurred in 9% of patients, with no grade ≥ 3 neurotoxicity observed. Genomic and transcriptomic data indicated that this regimen was effective across genetic subtypes and abrogated T‐cell exhaustion within the TME. However, tumour‐infiltrating M2 macrophages with dysregulated lipid metabolism were associated with poor clinical outcome. Conclusions Response‐adapted zanubrutinib and tislelizumab potentially enhances the efficacy of CAR T‐cell therapy with a favourable safety profile in R/R LBCL, effectively counteracting T‐cell exhaustion. Future studies should focus on targeting M2 macrophages by reprogramming lipid metabolism to further attenuate the immunosuppressive TME. Highlights Response‐adapted zanubrutinib plus tislelizumab potentially enhances the efficacy of CAR T‐cell therapy for R/R LBCL with acceptable safety profile. This regimen functions independently of genetic subtypes, rendering it more applicable for clinical practice with CAR T‐cell therapy. This regimen effectively abrogates T‐cell exhaustion, but fails to overcome the immunosuppressive effects of M2 macrophages, providing a rationale for remodelling TME to optimise CAR T‐cell therapy.